The effect of steel surface pretreatment on the adhesion bond between fly ash based geopolymer glue and steel substrates - Halas, Olena; Švanda, Pavel (Univerzita Pardubice, 2012)
This study deals with the investigation of fly ash based geopolymer glues. The main purpose was to study the effect of steel surface pretreatment on the adhesion bond between geopolymer glue and steel substrates. The surface of metal substrates was mechanically (sand blasting) and chemically (Interlox phosphate 2325 MCIZ or UniPrep PP) pretreated. It was also prepared two types of glues with different amount of sodium hydroxide. It was conducted single lap shear strength test in order to determine adhesive bond strength between geopolymer and steel. The test results showed that type of glue didn’t significantly influence on the strength, meanwhile the steel surface pretreatment had a considerable effect. The highest strength 2744KPa was reached using glue with smaller amount of sodium hydroxide and steel surface pretreatment by sand blasting and Interlox phosphate 2325 MCIZ.
Keywords: steel; fly ash; geopolymer glues